Effect of olive leaves extract on some physical and chemical traits of broiler meat during refrigeration storage - Hama, Arazu Abdullah (Journal of Kerbala for Agricultural Sciences, 2018)
This study was carried out to examine the effect of two concentration of natural olive leaves extract (OLE) 2 and 4% v/v, by application of two methods (spray and immersion) on some physical (water holding capacity and cooking loss), and chemical (thiobarbituric acid and free fatty acid) characteristics of broiler meat during refrigerate storage (4±1ᵒC) for 0, 2, 5 and 7 days. The treatments included: T1: (control), T2: 2% OLE spray, T3: 2% OLE immersion, T4: 4% OLE spray and T5: 4% OLE immersion. Water holding capacity (WHC) and cooking loss (CL) percentages showed significantly differences (p≤0.01) among treatments after 5 and 7 days storage, the highest WHC value (43.500%) recorded in T5 after 5 days storage when sample was treated with 4% OLE emersion compared with control treatment which recorded the lowest WHC value (34.200%) after 7 days storage. For CL after 5 days storage T4 recorded lower value (38.170%) compared to T2 (42.920%), whereas after 7 days storage T5 recorded lower CL value (42.380%) compared to T1(48.015%) and T2 (46.285%). Thiobarbituric acid (TBA) value decreased significantly (p≤0.01) with using of OLE after 7 days storage, and the highest value recorded in T1 (1.410 mg malonaldehyde/kg). Also there were a positive effect of OLE on free fatty acid (FFA) value after 2, 5 and 7 days of storage , after 2 days storage T5 recorded lest FFA value (0.381%), while the highest value recorded in T1 (0.925%). Also after 5 and 7 days storage OLE treatments recorded lower FFA value compared to T1 which recorded the highest value (1.150%) after 7 days storage. These results suggested that using of olive leaves extract as natural antioxidant to improve broiler meat quality characteristics and extend shelf-life during refrigerate storage, which may have implications of meat processors.